2023
DOI: 10.3389/fcimb.2023.1148383
|View full text |Cite
|
Sign up to set email alerts
|

Cell lipid biology in infections: an overview

Luan Gavião Prado,
Niels Olsen Saraiva Camara,
Angela Silva Barbosa

Abstract: Lipids are a big family of molecules with a vast number of functions in the cell membranes, within the cytoplasm, and extracellularly. Lipid droplets (LDs) are the most common storage organelles and are present in almost every tissue type in the body. They also have structural functions serving as building blocks of cellular membranes and may be precursors of other molecules such as hormones, and lipoproteins, and as messengers in signal transduction. Fatty acids (FAs), such as sterol esters and triacylglycero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 134 publications
(168 reference statements)
0
1
0
Order By: Relevance
“…Using RNA sequencing and shotgun lipidomics, we found that HAECs exposed to DF have an inflammatory transcriptional signature and increased cellular lipid content compared to HAECs exposed to UF. Increased lipid accumulation has previously been reported in other cell types exposed to stress conditions, including viral infection-mediated inflammation 29 . Furthermore, in human microvascular ECs, the expression of the FA transporter CD36 increased in response to viral infection 30 .…”
Section: Discussionmentioning
confidence: 75%
“…Using RNA sequencing and shotgun lipidomics, we found that HAECs exposed to DF have an inflammatory transcriptional signature and increased cellular lipid content compared to HAECs exposed to UF. Increased lipid accumulation has previously been reported in other cell types exposed to stress conditions, including viral infection-mediated inflammation 29 . Furthermore, in human microvascular ECs, the expression of the FA transporter CD36 increased in response to viral infection 30 .…”
Section: Discussionmentioning
confidence: 75%